Sudden Commencements and Geomagnetically Induced Currents in New Zealand: Correlations and Dependance - A. W. Smith; C. J. Rodger; D. H. Mac Manus; I. J. Rae; A. R. Fogg; C. Forsyth; P. Fisher; T. Petersen; M. Dalzell (Space Weather)
Abstract Changes in the Earth's geomagnetic field induce geoelectric fields in the solid Earth. These electric fields drive Geomagnetically Induced Currents (GICs) in grounded, conducting infrastructure. These GICs can damage or degrade equipment if they are sufficiently intense—understanding and forecasting them is of critical importance. One of the key magnetospheric phenomena are Sudden Commencements (SCs). To examine the potential impact of SCs we evaluate the correlation between the measured maximum GICs and rate of change of the magnetic field (H′) in 75 power grid transformers across New Zealand between 2001 and 2020. The maximum observed H′ and GIC correlate well, with correlation coefficients (r2) around 0.7. We investigate the gradient of the relationship between H′ and GIC, finding a hot spot close to Dunedin: where a given H′ will drive the largest relative current (0.5 A nT−1 min). We observe strong intralocation variability, with the gradients varying by a factor of two or more at adjacent transformers. We find that GICs are (on average) greater if they are related to: (a) Storm Sudden Commencements (SSCs; 27% larger than Sudden Impulses, SIs); (b) SCs while New Zealand is on the dayside of the Earth (27% larger than the nightside); and (c) SCs with a predominantly East‐West magnetic field change (14% larger than North‐South equivalents). These results are attributed to the geology of New Zealand and the geometry of the power network. We extrapolate to find that transformers near Dunedin would see 2000 A or more during a theoretical extreme SC (H′ = 4000 nT min−1).